Historia de una gesta libertadora 1952-1958; prologo [por] Fidel Castro Ruz - Pagán, Georgina Leyva (Editorial de Ciencas Sociales La Habana, 2014)
Presents unpublished data for the period 1952-58. Gives a brief review of Guantanamo.\n